Kupffer cell-expressed membrane-bound TNF mediates melphalan hepatotoxicity via activation of both TNF receptors - Kresse, Matthias; Latta, Markus; Künstle, Gerald; Riehle, Hans-Martin; van Rooijen, Nico; Hentze, Hannes; Tiegs, Gisa; Biburger, Markus; Lucas, Rudolf; Wendel, Albrecht (Journal of Immunology, 2005)
Isolated hepatic perfusion of nenresectable liver cancer using the combination of TNF and melphalan can be associated with a treatment-related hepatotoxicity. We investigated whether, apart from TNF, also melphalan is cytotosic in primary murine liver cells in vitro and investigated mediators, mode of cell death, and cell types involved. Melphalan induced a caspase-dependent apoptosis in hepatocytes, which was not seen in liver cell preparations depleted of Kupffer cells. Neutralization of TNF prevented melphalan-induced apoptosis and liver cells derived from mice genetically deficient in either TNFR 1 or 2, but not from lpr mice lacking a functional CD95 receptor, were completely resistant. Cell-cell contact between hepatocytes and Kupffer cells was required for apoptosis to occur. Melphalan increased membrane-bound but not secreted TNF in Kupffer cells and inhibited recombinant TNF-α converting enzyme in vitro. Melphalan induced also severe hepatotoxicity in the isolated recirculating perfused mouse liver from wild-type mice but not from TNFR 1 or 2 knockout mice. In conclusion, this study shows that melphalan elicits membrane TNF on Kupffer cells due to inhibition of TNF processing and thereby initiates apoptosis of hepatocytes via obligatory activation of both TNFRs. The identification of this novel mechanism allows a causal understanding of melphalan-induced hepatotoxicity. Copyright © 2005 by The American Association of Immunologists, Inc.